No Difference in Knee Kinematics Between Anterior Cruciate Ligament–First and Posterior Cruciate Ligament–First Fixation During Single-Stage Multiligament Knee Reconstruction: A Biomechanical Study. Issue 9 (28th September 2022) - Fayed, Aly M.; Kanto, Ryo; Price, Taylor M.; DiNenna, Michael; Linde, Monica A.; Smolinski, Patrick; van Eck, Carola
Background: For combined reconstruction of both the anterior cruciate ligament (ACL) and the posterior cruciate ligament (PCL), there is no consensus regarding which graft should be tensioned and fixed first. Purpose: The purpose of this study was to determine which sequence of graft tensioning and fixation better restores normal knee kinematics. The hypothesis was that ACL-first fixation would more closely restore normal knee kinematics, graft force, and the tibiofemoral orientation in the neutral (resting) position compared with PCL-first fixation. Study Design: Controlled laboratory study. Methods: A total of 15 unpaired human cadaveric knees were examined using a robotic testing system under the following 4 conditions: (1) 89.0-N anterior tibial load at different knee angles; (2) 89.0-N posterior tibial load at different knee angles; (3) combined rotational 7.0-N·m valgus and 5.0-N·m internal rotation load (simulated pivot shift) at 0°, 15°, and 30° of flexion; and (4) 5.0-N·m external rotation load at 0°, 15°, and 30° of flexion. The 4 evaluated knee states were (1) intact ACL and PCL (intact), (2) ACL and PCL deficient (deficient), (3) combined anatomic ACL-PCL reconstruction fixing the ACL first (ACL-first), and (4) combined anatomic ACL-PCL reconstruction fixing the PCL first (PCL-first). A 9.0 mm–diameter quadriceps tendon autograft was used for the ACL graft, tensioned with 40.0 N at 30° of flexion. A 9.5 mm–diameter hamstring tendon autograft (gracilis and semitendinosus, quadrupled loop, and augmented with an additional allograft strand if needed), tensioned with 40.0 N at 90° of flexion, was used for the PCL graft. Results: There were no statistically significant differences between ACL-first and PCL-first fixation regarding knee kinematics. ACL-first fixation restored anterior tibial translation to the intact state at all tested knee angles, while PCL-first fixation showed higher anterior tibial translation than the intact state at 90° of flexion (9.05 ± 3.05 and 5.87 ± 2.40 mm, respectively; P = .018). Neither sequence restored posterior tibial translation to the intact state at 30°, 60°, and 90° of flexion. At 15° of flexion, PCL-first fixation restored posterior tibial translation to the intact state, whereas ACL-first fixation did not. Conclusion: There were no differences in knee laxity between ACL-first and PCL-first fixation with the ACL graft fixed at 30° and the PCL graft fixed at 90°. Clinical Relevance: This study showed that there was no evidence to support the use of one tensioning sequence over the other in single-stage multiligament knee reconstruction.